Association between lifestyle and dietary preference factors and conventional adenomas and serrated polyps - Xu, Jue; Chi, Peihan; Qin, Kang; Li, Biao; Cheng, Zhongxue; Yu, Zhecong; Jiang, Caixia; Yu, Yunxian (Frontiers in Nutrition, 2024)
Introduction Both conventional adenoma (AD) and serrated polyp (SP) were known precursor lesions of colorectal cancer (CRC). Modifiable lifestyle factors were significantly associated with CRC risk, but whether these factors were related to the risk of different precursors of CRC needed to be clarify. This study aimed to evaluate the risks of AD and SP caused by lifestyle factors, and compare the risk differences between AD and SP. Methods The study population was from the CRC screening cohort in Hangzhou, China. A total of 458,457 eligible individuals volunteered to undergo initial screening including the fecal immunochemical test (FIT) and the CRC risk assessment. Finally, 13993 participants who had undergone colonoscopy test and had diagnosed at designated hospitals were selected in this study. All participants were required to fill out a questionnaire in initial screening for collecting their information. The generalized estimate equation (GEE) model was used to assess the association between lifestyle factors/dietary preferences and AD/SP. Results The body mass index (BMI) and smoking were positively associated with the risks of only SP (BMI: OR=1.50, 95%CI:1.23-1.84; smoking: OR=1.29, 95%CI:1.07-1.55), only AD (BMI: OR=1.53, 95%CI:1.28-1.82; OR=1.24, 95%CI:1.11-1.39) and synchronous SP and AD (BMI: OR=1.97, 95%CI:1.40-2.75; smoking: OR=1.53, 95%CI:1.27-1.85). In the case-group comparison, smoking was more strongly associated with the risk of synchronous SP and AD than only AD. Alcohol drinking was positively associated with the risk of AD (OR=1.28, 95%CI:1.14-1.44), but no statistically significant difference was observed in risks in case-group comparison. Further, whole grain intake was associated with a decreased risk of only AD (OR=0.78, 95%CI: 0.65-0.93). While white meat intake was positively associated with risks of only SP when compared with AD cases (OR=1.60, 95%CI: 1.15-2.23). Conclusion The current study identified common risk factors such as BMI and smoking, as well as different risks of certain factors (e.g. alcohol drinking, whole grains intake) for SP and AD. But there were still some factors, especially diet-related factors, that have not been fully elucidated in their association with the two lesions. Further research is needed in the future to confirm and develop prevention strategies for different lesions.